2016
DOI: 10.21275/v5i5.nov163185
|View full text |Cite
|
Sign up to set email alerts
|

Linkage Effects of Rural Non-Farm Income Diversification on Poverty Reduction among Farm Households in Southeast, Nigeria

Abstract: Abstract:The incidence of poverty in rural communities of Nigeria like many other African countries is very severe and breaking the incidence requires diversification into non-farm activities which no documented empirical records seems to exist in Southeast Nigeria. In addressing the problem, the study measured the poverty status of the rural farm households; determined the effect of non-farm income diversification on the poverty reduction level of the rural farm households; and determined the linkage effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In line with these findings, Odoh et al (2020) found a lower level of income generation from farm activities than non-farm activities. Odoh and Nwibo (2016) also found that in Nigeria non-farm sector is a major contributor to employment and income generation of rural households, contributing up to 63% of household income.…”
Section: Factors Influencing Ict and Access To Creditmentioning
confidence: 97%
“…In line with these findings, Odoh et al (2020) found a lower level of income generation from farm activities than non-farm activities. Odoh and Nwibo (2016) also found that in Nigeria non-farm sector is a major contributor to employment and income generation of rural households, contributing up to 63% of household income.…”
Section: Factors Influencing Ict and Access To Creditmentioning
confidence: 97%